Luce Irigaray and the philosophy of sexual difference - Stone, Alison, 1972- (Cambridge University Press, 2006)
"This book offers a feminist defence of the idea that sexual difference is natural. Providing a new interpretation of the later philosophy of Luce Irigaray, Alison Stone defends Irigaray's unique form of essentialism and her rethinking of the relationship between nature and culture. She also shows how Irigaray's ideas can be reconciled with Judith Butler's performative conception of gender by rethinking sexual difference in relation to German Romantic philosophies of nature. This is the first sustained attempt to connect feminist conceptions of embodiment to German Idealist and Romantic accounts of nature. Not merely an interpretation of Irigaray, this book also presents an original feminist perspective on nature and the body. It will encourage debate on the relations among sexual difference, essentialism, and embodiment."--Jacket